Popoff Strait and Humboldt Harbor, Alaska / surveyed by W.H. Dall, Act'g. Assist. - United States Coast Survey (1872)
Relief shown by hachures. Depths shown by soundings. Includes navigational notes. "No. 11" -- upper right margin 1:40,000